Brine Shrimp Lethality and Antioxidant Activity of the Leaf, Rind and Seed Ethanolic Extracts of Durio zibethinus L. - Ang, Aileen May Gabule; Nalda, Cherry Mae Delos Reyes; Sabejon, Sandra Espinosa (Asian Journal of Biological and Life Sciences, 2018)
Introduction:Substances derived from plants have recently receiving renewed interest due to their versatile applications. Parts ofDurio zibethinusL. have been used traditionally as remedy to many diseases. To date, limited reports on the cytotoxicity and antioxidative property ofD. zibethinusparts are available.Objective:The study aims to determine the cytotoxic and antioxidative property of the leaf, seed and rind ethanolic extracts ofD. zibethinusL. Materials and Methods: Cytotoxicity of the leaf, seed and rind ethanolic extracts ofD. zibethinusL. were determined through Brine Shrimp Lethality Assay (BSLA) while antioxidative property were measured via 2,2-diphenyl-1-picrylhydrazyl (DPPH) Radical Scavenging Activity and Reducing Power Assay.Results and Discussions:Results of the BSLA showed that the LC50value of the ethanolic leaf, rind and seed extracts are 624.00, 139.31 and 46.28 mg/L, respectively. The data indicate potential cytotoxic property of the rind and seed extracts which can be attributed to the anthraquinones, flavonoids, phenolics, saponins and terpenoids detected in the rinds and seed extracts. The effective concentration (EC50) value for the DPPH radical scavenging activity and reducing power for the seed and rind ethanolic extracts showed significantly higher activity compared to the leaf extract. Similarities in the trend of the DPPH inhibition and reducing power of the ethanolic extracts of the leaves, rinds and seed ethanolic extracts imply direct correlation between DPPH scavenging activity and reducing power (P<0.01).Conclusion:D. zibethinusseeds and rinds can be potential sources of natural cytotoxic and antioxidant compounds.
Keywords: Antioxidant property; BSLA; cytotoxicity; DPPH; Durio zibethinus